The influence of sensation seeking behavior and social media addiction on happiness among young adults in Malaysia - Titus, David Rasahpandy; Maria Peter, Micheal; Ashwinie Nair, Sridharan Nair (2021)
The happiness level among young adults has been degenerating across the globe and Malaysia has been ranked to be at a concerning place. This study aims to investigate the influence of sensation seeking behavior and social media addiction on happiness among young adults in Malaysia. The hypotheses of this present study are happiness level is low among young adults, sensation-seeking has a significant positive relationship with happiness, and social media addiction has a significant negative relationship with happiness among young adults in Malaysia. The sample size comprised 315 active social media users aged between 18 to 30 who lives in Malaysia and 30 participants in the pilot study. The study was conducted online via Qualtrics software. This descriptive research study involves Oxford Happiness Questionnaire. Brief Sensation Seeking Scale, and Bergen Social Media Addiction Scale. The data was gathered by identifying the target group on social media and promoting e-posters. Next, registration form alongside with informed consent and others were sent to the participants. The collected data was analysed using SPSS software. Results suggest a significant low level of happiness, high level of sensation-seeking behaviour with significant positive relationship with happiness, and significant negative relationship between social media addiction and happiness among the participants. All the results of this present study are in line with past studies. Sensation-seeking behaviour and social media addiction affect happiness and addressing any one of these possible influences is likely to contribute to the literature gap and increase happiness among young adults in Malaysia.